Modeling national innovation system enabled by knowledge management - Chu, Mei-Tai; Rezaeian Fardoei, Sedigheh; Fallah, Hasan; Ghazinoory, Sepehr; Aliahmadi, Alireza (Journal of Business Economics and Management, 2014)
The main objective of this paper is to explore the model of how knowledge management functions enables national innovation system. To achieve the objectives of the study, a conceptual framework is proposed and described, then the systemic analysis is undertaken. Path coefficient and t-value are also used to measure the relationships among chosen variables. A great number of sources are used to collect data, including questionnaires, interviews, observations, and literature review. The achievements of the study demonstrate 10 distinctive national innovation system performance dimensions and the relationship with knowledge management functions. The first layer includes explicit knowledge, while the second layer deals with tacit knowledge. Both of two layers link to a complete knowledge management functions and processes: explicit knowledge building, explicit knowledge gathering, explicit knowledge distributing, explicit knowledge reusing, tacit knowledge capturing, tacit knowledge sharing tacit knowledge disseminating, tacit knowledge innovating; whereas the third layer includes NIS enablers items or performance dimension of national innovation system: quality, effectiveness, quantity, codification, structure, efficiency, internalization, expertise, effectiveness.